2021
DOI: 10.1186/s40959-021-00093-z
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic myocardial strain analysis describes subclinical cardiac dysfunction after craniospinal irradiation in pediatric and young adult patients with central nervous system tumors

Abstract: Background Craniospinal irradiation (CSI) is part of the treatment of central nervous system (CNS) tumors and is associated with cardiovascular disease in adults. Global myocardial strain analysis including longitudinal peak systolic strain (GLS), circumferential peak systolic strain (GCS), and radial peak systolic strain (GRS) can reveal subclinical cardiac dysfunction. Methods Retrospective, single-center study in patients managed with CSI vs. ag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Changes in GLS have been shown be an early indicator of cardiac dysfunction in CCS. [12][13][14][15][16] However, retrospective analysis of GLS as a predictive measure of heart failure development is limited by only having single plane apical 4-chamber views recorded in many older archived studies. This was the most common reason GLS as measured from three apical planes with 2D speckle tracking could not be determined in a previous GLS analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in GLS have been shown be an early indicator of cardiac dysfunction in CCS. [12][13][14][15][16] However, retrospective analysis of GLS as a predictive measure of heart failure development is limited by only having single plane apical 4-chamber views recorded in many older archived studies. This was the most common reason GLS as measured from three apical planes with 2D speckle tracking could not be determined in a previous GLS analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial strain is a noninvasive measurement on 2-dimentional speckle tracing ECHO, it is reported as a percent that can be measured by global longitudinal strain (GLS), global circumferential strain (GCS) and global radial strain (GRS). Prior studies have demonstrated decreased GLS and GSC despite normal left ventricular EF or SF in childhood cancer survivors, implying presence of LV systolic dysfunction or subclinical myocardial dysfunction [35][36][37][38][39]. Reduction in GLS by 10 to 15% appears to be the most useful parameter for prediction of cardiotoxicity, as it may de ne a decrease in LVEF or heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…The true value in predicting subsequent ventricular dysfunction or heart failure needs to be further evaluated. In a recent article by Martinez et al, the ECHO results from 51 patients treated for pediatric CNS malignancies at Cincinnati Children's Hospital with CSI who had at least one ECHO done after CSI, did not have abnormal left ventricular dysfunction noted [39]. However, abnormal cardiac strain was demonstrated [39].…”
Section: Discussionmentioning
confidence: 99%
“…Left ventricular systolic dysfunction has been extensively investigated and has been linked to suboptimal outcomes while undergoing cancer management [ 21 , 47 ]. In children, EF% and strain analysis remain the surrogate markers to evaluate ventricular dysfunction [ 3 , 14 , 48 , 49 ]. Global longitudinal strain has been reported to be the most efficient strain parameter to quantify left ventricular mechanics.…”
Section: Surveillance and Managementmentioning
confidence: 99%
“…Global longitudinal strain has been reported to be the most efficient strain parameter to quantify left ventricular mechanics. In our experience, it has been helpful to identify focal and global ventricular dysfunction although we recommend reviewing vendor-specific values of normal/abnormal when using it clinically [ 14 , 48 , 50 ]. When the ventricular systolic function is suboptimal at the regional or global levels, the use of beta-blockers (BB), angiotensin-converting-enzyme inhibitors (ACEIs), and angiotensin receptor blockers (ARBs) has been associated with cardio protection [ 3 , 21 , 51 , 52 ].…”
Section: Surveillance and Managementmentioning
confidence: 99%